Investigating Molluscum Contagiosum Virus Protein MC009 as a Novel Inhibitor of Human Innate Immune Signalling - Kusiak, Aleksandra Helena (Trinity College Dublin. School of Medicine. Discipline of Immunology, 2024)
Molluscum contagiosum virus (MCV) is a human-adapted poxvirus that causes mild, raised skin lesions which are highly contagious. The lesions are notable for exerting minimal to no inflammation but can persist for long durations of time without an effective anti-viral response from the host. Human innate signalling pathways are targeted by MCV encoded immunomodulators, such as MC005 and MC132. These cascades regulate two major transcription factor families responsible for driving an anti-viral immune response, the nuclear factor kappa B (NF-kB) and the interferon regulatory factor (IRF) members. These transcription factors require an importin/karyopherin shuttle to translocate into the nucleus in order to upregulate inflammatory and gene expression in response to infection. To date, less than 15 MCV proteins have been thoroughly researched and their immunomodulatory function understood. Furthermore, the role of karyopherin proteins is not well described during MCV pathogenesis and immune evasion. MC009 was previously identified as a Molluscipoxvirus specific protein by the lab, however its mechanism of action had not been defined. Pathway mapping conducted using gene reporter assays determined MC009 to be an inhibitor of pattern recognition receptor (PRR)- and cytokine-induced kB- and IRF-luciferase activity. MC009-driven inhibition resulted in reduced IL-8, IP-10 and IFN-B production and IFN-B-luciferase activity. Following this discovery, the mechanism of function was investigated. Three hypotheses were studied to understand the diminished pro-inflammatory cytokine and type I IFN production. Firstly, an MC009-p65 interaction was investigated, however, there was no indication of the two proteins directly interacting with each other. The phosphorylation of IkB was examined next which was not altered in cells expressing MC009. Lastly, transcription factor nuclear translocation was studied. MC009 detained p65 within the cytoplasm after TNFa induction, preventing p65 from translocating into the nucleus. NF-kB members depend on karyopherin proteins to transport across the nuclear membrane. Using confocal microscopy and co-immunoprecipitation (Co-IP) techniques, MC009 was observed to interact with overexpressed and endogenous karyopherin subunit a 6 (KPNA6). A strong interaction between MC009 and KPNA5 and a weaker interaction with KPNA1 were also observed. MC009 disrupts p65-mediated immune responses through KPNA function interference. Furthermore, the interaction between MC009 and KPNA6 did not inhibit KPNA6-p65 binding, but rather formed a p65-KPNA6-MC009 complex. The protein complex likely sequesters within the cytoplasm as MC009 was not observed translocating into the cell nucleus with endogenous KPNA6. In this thesis, I present MC009 as a potent inhibitor of both NF-kB and IRF3/7 signalling, a mechanism through which MCV inhibits the activation of pro-inflammatory and anti-viral immune responses. The inhibitor causes major disturbances to human immune gene regulation by p65 cytoplasmic sequestration. I report MC009 as the first MCV-derived immunosuppressor and only second known poxviral protein capable of signal inhibition by directly targeting karyopherin proteins. MC009 offers novel insights into human innate signalling whilst broadening our understanding of MCV immune evasion strategies.
APPROVED
Keywords: Innate Immunity; Molluscum contagiosum virus; Innate signalling; Immune evasion; Immunology; MCV; Signalling; TLRs; RLRs; cGAS; KPNA6; Karyopherin; Importin; NF-kB; IRF family